INNOVATION OF FISH CRACKER PRINTING MACHINE FOR PRODUCTION PROCESS EFFICIENCY - Alghifari, Muhammad Romadhon; Murnawan, Hery (Universitas Islam Nahdlatul Ulama Jepara, 2025)
UMKM Rejeki Barokah which is engaged in the production of mackerel fish crackers with the brand